Analisis Kepuasan Driver Terhadap Aplikasi Maxim Menggunakan Metode End User Computing Satisfaction (EUCS) - Muhamad Ariandi; Dila Marsolina (JURIKOM (Jurnal Riset Komputer), 2023)
Maxim is here as a new innovation and as a competitor in the world of online transportation. However, this application has not fully provided service satisfaction to driver partners. This study aims to analyze driver satisfaction with the Maxim application using the End User Computing Satisfaction (EUCS) method. The problem faced is the high level of driver complaints against the Maxim application which has the potential to reduce the quality of online transportation services. This indicates that there is user dissatisfaction with the features available in the Maxim application. Therefore, it is necessary to analyze driver satisfaction with the Maxim application to find out the factors that influence user satisfaction. The EUCS method is used to measure driver satisfaction with the Maxim application using 5 variables, namely content(X1), Accuracy(X2), Format(X3), Ease of use(X4) and Timelines(X5). So that the level of satisfaction (Y) from maxim application users is more measurable, so as to generate input for system developers and developers. This research was conducted by taking a sample of 100 drivers in the city of Palembang by random sampling. The results of the research conducted show that driver satisfaction with the Maxim application is at a fairly good level, with an average satisfaction score of 3.67 out of a scale of 5. With this value, the company needs to improve the development of features related to Maxim application users. The results of this study can be input for the company in improving the quality of the Maxim application service, so that it can meet the needs and satisfaction of its users. So that in the future the Maxim company itself wants to compete with fellow online transportation service entrepreneurs in serving the service users offered.